Acceptability and adoption of health-facility based NCD surveillance in Kulon Progo district, Yogyakarta - Theodola Baning Rahayujati (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Background: Non-communicable diseases (NCD) have been recognized as the new disease pandemic to the developing world in recent years. In 2020, it is estimated that 70% of NCD-related deaths will occur in developing countries. The most prevalent NCD such as coronary heart diseases, cancer, respiratory diseases and diabetes mellitus. Since 2012 Indonesia MOH was established two main surveillance system i.e. health facility- and community-based surveillance systems. MOH report on 2015 showed those reporting from PHC less than 25%. The front-line of health facility-based surveillance is the primary health centers (PHC). Data should undergo validity and quality check by the District and Provincial Health Office before being sent to the central reporting system.This study aim to evaluate the implementation of health-facility based NCD surveillance and develops recommendations for increasing coverage NCD surveillance in Kulon Progo District. Method: We used RE-AIM (only Reach and Adoption) framework for evaluating the surveillance system. The Reach variables are coverage, knowledge, acceptance, constraint, infrastructure and feasibility. 76 NCD team at PHC and District Health office included doctor, nurse, program manager and laboratory staffs were interviewed and observed using a standardize questionnaire and checked list. Secondary data on NCD surveillance reports were collected and reviewed. Qualitative study were conducted through semi structured interviews and FGDs to evaluate acceptance, constraints and barriers of implementation. Descriptive analysis was used to analyze quantitative data and content analysis was performed on the qualitative data. Result: This study found that most of the health officer involving in the non-communicable program was having fair knowledge on web based NCD surveillance, and only 5% of the respondent has a good understanding on it. There are 19 Puskesmas was assessed on the completeness of the data entry on web based NCD surveillance.